(untitled) (Journal of Educational Sciences, 2016)
Мақалада шетелдік елдердің əдебиеттіндегі құжаттар жəне түрік əдебиет құжаттарды оқытудағы сабақтастығы қарастырылған. Modern globalization, inte rnational integration, innovations taken place in the pedagogical system require to create structural connections between all components of the training as a didactic principle. Literature teaching in the world countries is accepted as a main factor for formation of the national thinking. In the programs and text – books compiled for years for Turkish and foreign country materials – works of Literature coryphaeus, fairy, tales, mythology. The pupil makes aguaintance with other people folk-lore, such as: “What is fore ever ?” (Turkish); “Ahmet and King” (Uzbek); “Prometey” (Greece); “Syndibat” (Arabic). They master humanist ideas to the representatives of the other people by the force of friction.